Pengaruh Carbon Emission Disclosure dan Ukuran Perusahaan Terhadap Kinerja Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2021-2023 - Rahmatania, Alvina; Wardhani, Rulyanti Susi; Sumiyati, Sumiyati (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Company performance is a result obtained by the company through various kinds of company operational activities within a certain period of time as a company effort to generate maximum profits.  This research aims to test and analyze the influence of carbon emission disclosure and company size on the performance of manufacturing companies on the BEI in 2021-2023.  The population in this study was 170 companies and the research sample was 40 companies taken using the purposive sampling method.  The research results show that carbon emission disclosure and company size have a negative effect on company performance.